2007
DOI: 10.1001/archpsyc.64.9.999
|View full text |Cite
|
Sign up to set email alerts
|

Selective Abnormal Modulation of Hippocampal Activity During Memory Formation in First-Episode Psychosis

Abstract: Context: Memory is one of the cognitive functions most affected in schizophrenia, with deficits observed from the first episode of psychosis (FEP). Previous studies have indicated that some memory processes may be more affected than others.Objective: To examine the neural correlates of 3 specific memory processes in FEP by means of functional magnetic resonance imaging (fMRI).Design: Case-control study. Main Outcome Measures:Behavioral performance and regional brain activity measured during memory encoding by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 85 publications
(90 reference statements)
11
43
0
Order By: Relevance
“…[67][68][69][70][71][72][73][74][75][76][77][78] By contrast, task-related MTL activation, measured with funtional magnetic resonance imaging (fMRI) blood-oxegen-level dependent (independent of baseline) and representing regional responses to task demands and performance, is reduced in schizophrenia, with reductions observed during processing of novel stimuli, verbal memory encoding, and associative encoding. [79][80][81][82][83][84][85][86][87][88] We have suggested that the 2 are related-that the blunted activation to task demand is secondary to the increased perfusion at baseline. 10 As such, it is the elevated perfusion in schizophrenia that requires a mechanistic explanation; elevated perfusion is taken to represent an increase in excitatory neuronal activity.…”
Section: Functional Hippocampal Imaging In Schizophreniamentioning
confidence: 99%
“…[67][68][69][70][71][72][73][74][75][76][77][78] By contrast, task-related MTL activation, measured with funtional magnetic resonance imaging (fMRI) blood-oxegen-level dependent (independent of baseline) and representing regional responses to task demands and performance, is reduced in schizophrenia, with reductions observed during processing of novel stimuli, verbal memory encoding, and associative encoding. [79][80][81][82][83][84][85][86][87][88] We have suggested that the 2 are related-that the blunted activation to task demand is secondary to the increased perfusion at baseline. 10 As such, it is the elevated perfusion in schizophrenia that requires a mechanistic explanation; elevated perfusion is taken to represent an increase in excitatory neuronal activity.…”
Section: Functional Hippocampal Imaging In Schizophreniamentioning
confidence: 99%
“…This is consistent with a model in which activation is constitutive. More recently, using a cohort of first-episode psychosis patients, the deficit in hippocampal activation was shown to be relatively specific to the encoding of semantic 'relatedness' (whether images were related in content or not), arguing against a general inability to recruit the hippocampus [49] . However, cerebrovascular-based measures of activation such as BOLD and rCBF are illsuited to detect chronic hyperactivity of the hippocampus, the condition suggested by excessive phasic DA release.…”
Section: The Hyperactive Hippocampus In Schizophreniamentioning
confidence: 99%
“…NMDA receptors (NMDAR) are synaptic coincidence detectors (Bliss and Collingridge 1993) and therefore essential for long term potentiation, which is itself a basis for learning and memory consolidation (Chen and Tonegawa 1997;Shimizu et al 2000). Reduced NMDAR function has been implicated as a model for schizophrenia pathology (Olney and Farber 1995;Greene 2001;Konradi and Heckers 2003) and in vivo imaging studies have provided evidence of aberrant hippocampal recruitment during tasks of episodic memory (Heckers et al 1998;Weiss et al 2003) and memory formation (Achim et al 2007). …”
Section: Schizophrenia Pathophysiologymentioning
confidence: 99%